Analisis Implementasi Layanan Digital Dan Manajemen Arsip - Ayuni Rahmawati; Nurfatiah; Azzara; Kamaruzaman; Wahyuni Jamil (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2026)
Internships within the framework of the Independent Learning Campus (MBKM) program provide a strategic platform for students to actualize their academic competencies in the context of the professional workplace. This study analyzes the experience of implementing an internship in the service department of PT. TASPEN (Persero) Tanjungpinang Branch Office for four months (February–May 2026), focusing on three main aspects: claim submission through the TOOS (Taspen One Hour Online Service) system, digital archive management (scanning and Electronic Leitz Ordner/ELO), and physical archive management. A descriptive-analytical approach was used to analyze operational processes and their impact on service efficiency. The results show that the integration of digital technology in the TOOS system significantly improves service accessibility and accelerates the claims process, despite facing user adaptation barriers. Digital archive management through ELO optimizes document storage and retrieval, while physical archive management remains relevant for administration and verification. In conclusion, the hybrid implementation of digital and physical document management systems creates a stronger, more customer-centric service ecosystem.  These findings demonstrate the importance of digital transformation that does not completely abandon traditional mechanisms in the context of public services.